Chemical Reaction Mechanism between A-Site Deficient La Substituted SrTiO3 and PH3 in Coal Syngas. Issue 12 (1st January 2015) - Chen, Gang; Kishimoto, Haruo; Yamaji, Katsuhiko; Kuramoto, Koji; Gong, Mingyang; Liu, XingBo; Hackett, Gregory; Gerdes, Kirk; Horita, Teruhisa
Abstract : Reactivity between a series of A-site deficient La substituted SrTiO3 (LST) and 1 ppm PH3 contained in coal syngas was investigated. Four LST pellets with different A-site deficiencies were annealed in simulated coal syngas and in simulated coal syngas containing 1 ppm PH3 at 900°C for 100 hrs, respectively. XRD and SEM/EDS results indicate that each pellet had reacted with PH3 . Little LaPO4, and much Sr3 (PO4 )2 and TiO2 were found on the surface of stoichiometric LST-1. No LaPO4 but Sr3 (PO4 )2 and TiO2 were observed on the surface of other A-site deficient specimens including LST-0.95, LST-0.9 and LST-0.85 after the exposure test. Chemical stability of LST for PH3 was effectively improved by reducing the A-site deficient composition. Sr located at grain boundaries on the surface of each LST pellet was found to possess the highest reactivity with PH3, and diffusion of Sr in the grain boundaries of LST and in Sr3 (PO4 )2 formed on the surface of LST facilitated the whole reaction. Sr consumption in LST resulted in precipitation of TiO2 and formation of LaPO4 . The decrease of Sr and La chemical potentials with the increasing of A-site deficiency in LST was the dominant reaction suppression mechanism.